An AIEgen-based hydrazone-linked covalent organic polymer for solid-state fluorescent materials. (October 2022) - Wang, Ruitong; He, Chunni; Xu, Zejun; Lei, Yihui; Jiang, Yu; Zhang, Junheng; Chen, Sufang; Zhang, Daohong
Abstract: The construction of high quantum yield solid-state fluorescent materials is of great importance in preparing organic light-emitting devices. Herein we report an AIEgen-based emissive hydrazone-linked covalent organic polymer (TFBE-TD COP) prepared by a simple solid-state mechanochemical grinding method from 1, 1, 2, 2-tetrakis(4-formyl-(1, 1′-biphenyl))ethane (TFBE) and terephthalic tihydrazide (TD) at room temperature. The COP exhibits good emission and very high fluorescence quantum yield ( Φ F  = 37.7%) in the solid-state because of the synergistic effect of rigid skeleton structure and aggregation induction that restricts the relaxation of tetraphenylethylene (TPE) molecules in the TFBE-TD COP. TFBE-TD COP shows a rapid response and high sensitivity toward trifluoroacetic aid (TFA) gas with significant changes in visual color and luminescence, which could be recovered upon exposure to triethylamine vapor. And the TFBE-TD COP was further coated onto the blue LED to achieve white-light emission. The work provides a general method for preparing AIEgen-based COP and explores its applications in solid-state fluorescent materials for the sensing of toxic gases and the preparation of white LED, offering a new route to the design and application of AIEgen-based COPs. Graphical abstract: An AIEgen-based emissive hydrazone-linked covalent organic polymer (TFBE-TD COP) was prepared by a simple solid-state mechanochemical grinding method from 1, 1, 2, 2-tetrakis(4-formyl-(1, 1′- biphenyl))ethane (TFBE) and terephthalic tihydrazide (TD) at room temperature. The COP exhibits good emission and very high fluorescence quantum yield ( Φ F  = 37.7%) in the solid-state because of the synergistic effect of rigid skeleton structure and aggregation induction that restricts the relaxation of tetraphenylethylene (TPE) molecules in the TFBE-TD COP. TFBE-TD COP shows a rapid response and high sensitivity toward trifluoroacetic aid (TFA) gas with significant changes in visual color and luminescence, which could be recovered upon exposure to triethylamine vapor. And the TFBE-TD COP was further coated onto the blue LED to achieve white-light emission. The work provides a general method for preparing AIEgen-based COP and explores its applications in solid-state fluorescent materials for the sensing of toxic gases and the preparation of white LED, offering a new route to the design and application of AIEgen-based COPs. Image 1 Highlights: An AIEgen-based emissive hydrazone-linked covalent organic polymer (TFBE-TD COP) was prepared. The TFBE-TD COP exhibits good emission and very high fluorescence quantum yield (ΦF  = 37.7%) in the solid-state. The TFBE-TD COP shows a rapid response and high sensitivity toward trifluoroacetic aid (TFA) gas. The TFBE-TD COP was coated onto the blue LED to achieve white-light emission.